Efficacy and Safety of 0.15% Isobutylamido Thiazolyl Resorcinol Combined with Hyaluronic Acid versus 0.15% Isobutylamido Thiazolyl Resorcinol or Hyaluronic Acid Alone in Melasma Treatment: A randomized Evaluator-blind Trial - Disphanurat, Wareeporn; Srisantithum, Benjaporn (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Melasma is recalcitrant to treatments. A combination of isobutylamido thiazolyl resorcinol (ITR) and hyaluronic acid (HA) could increase melasma treatment efficacy. Objectives: To compare the efficacy and safety of 0.15% ITR plus HA versus 0.15% ITR, or HA alone in melasma treatment. Methods: Ninety-two patients were randomly divided into 3 groups to received 0.15% ITR plus HA (n = 30), 0.15 % ITR (n = 31), or HA (n = 31) to apply to the melasma-affected facial areas along with a broad-spectrum sunscreen application for 12 weeks. Treatment efficacy was determined by modified Melasma Area Severity Index (mMASI), average melanin and melanin variation by Antera3D®, and safety by trans-epidermal water loss. Results: Compared with HA, the ITR plus HA group showed significantly reduced mMASI at weeks 4, 8, and 12 (P = 0.026, 0.015, and 0.001, respectively); while the ITR group showed significant reductions at weeks 12 (P = 0.027). There was no significant difference in mMASI or average melanin levels between the ITR plus HA and ITR groups. However, melanin variation was significantly lower in the ITR plus HA than the ITR group at weeks 4, 8, and 12 (P = 0.027, 0.019, and 0.023, respectively). Conclusions: 0.15% ITR and 0.15% ITR plus HA effectively reduced melasma severity. HA could synergistically improve melasma homogeneity.